Guru PAK Sebagai Desainer Pendidikan - Tiur Imeldawati (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
Abstract: Management of education cannot be separated from the element of teachers as educators and teachers. The teacher designs a lesson and seeks to implement the ongoing curriculum in order to achieve educational goals. Teachers have an important role in the development of education, and in a special context, namely as teachers of Christian Religious Education. As a designer, the teacher makes patterns and prepares classroom management according to the planned pattern. In the task of designing, it takes creativity and innovation. Teachers need to equip themselves with various competencies so that they can become effective and professional teachers. The teacher is an educational designer that is very much needed by this country.Keywords: teacher; designer; christian religious education AbstrakPengelolaan pendidikan tidak mungkin terlepas dari unsur guru sebagai pendidik dan pengajar. Guru mendesain sebuah pembelajaran dan berupaya mengimplementasikan kurikulum yang sedang berlangsung demi mencapai tujuan pendidikan. Guru memiliki peran yang penting dalam pengembangan pendidikan, dan dalam konteks khusus yakni sebagai guru Pendidikan Agama Kristen. Sebagai seorang desainer, guru membuat pola dan mempersiapkan pengelolaan kelas sesuai dengan pola yang telah direncanakan. Dalam tugas mendesain, dibutuhkan kreatifitas dan inovasi. Guru perlu memperlengkapi diri dengan berbagai kompetensi sehingga bisa menjadi guru yang efektif dan profesional. Guru merupakan seorang desainer pendidikan yang sangat dibutuhkan oleh negeri ini.Kata kunci: guru, disainer; pendidikan agama kristen